2021
DOI: 10.3389/fonc.2020.617109
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Autophagic Processes and Cachexia: The Missing Link?

Abstract: Cachexia is a syndrome that affects the entire organism and presents a variable plethora of symptoms in patients, always associated with continuous and involuntary degradation of skeletal muscle mass and function loss. In cancer, this syndrome occurs in 50% of all patients, while prevalence increases to 80% as the disease worsens, reducing quality of life, treatment tolerance, therapeutic response, and survival. Both chronic systemic inflammation and immunosuppression, paradoxically, correspond to important fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Thus, our data support previous studies with adenoviruses and vaccinia viruses showing that OV can prevent the development of cancer cachexia [50][51][52]. Proinflammatory cytokines with catabolic actions, in particular, IL-6, IL-1β, TNFα and IFNγ, seem to be key mediators of cancer cachexia and it has been proposed that crosstalk between tumor cells, the immune system and the specific cell composition of the TME are crucial to the releasing of these factors [53,54]. In line with this, we observed a strong reduction of IL-1β expressing macrophages, NK cells, DC and CD3 + cells in the TME of PD-H-infected Colon-26 tumors demonstrating that the immunomodulating properties of PD-H contributed to the reduction of IL-1β-expressing immune cells, which may also affect cachexia development.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, our data support previous studies with adenoviruses and vaccinia viruses showing that OV can prevent the development of cancer cachexia [50][51][52]. Proinflammatory cytokines with catabolic actions, in particular, IL-6, IL-1β, TNFα and IFNγ, seem to be key mediators of cancer cachexia and it has been proposed that crosstalk between tumor cells, the immune system and the specific cell composition of the TME are crucial to the releasing of these factors [53,54]. In line with this, we observed a strong reduction of IL-1β expressing macrophages, NK cells, DC and CD3 + cells in the TME of PD-H-infected Colon-26 tumors demonstrating that the immunomodulating properties of PD-H contributed to the reduction of IL-1β-expressing immune cells, which may also affect cachexia development.…”
Section: Discussionsupporting
confidence: 89%
“…An increasing number of studies have shown that the TME has a crucial impact on tumor progression, immunotherapy response, and immune escape (20,21). Recently, one research has also showed that under a scenario of balanced autophagy in the tumor microenvironment, the infiltrating immune cells control cytokine production and secretion (22). Sacco et al indicated that tumor-infiltrating immune cells could affect the tumor immunosurveillance by regulating the iron metabolism (23).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that the size of cancerous tissue is not associated with the presence of cachexia, but that the stage of cancer can affect the severity of cachexia. The prevalence of cancer cachexia is approximately 50% in all patients with cancer, increasing to 80% according to the disease progression [5]. Almost 80% of patients with gastric or pancreatic cancer and 50% of patients with lung, prostate, or colon cancer experience cachexia.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of cancer cachexia is systemic inflammation caused by the interaction between tumor and organ tissues, resulting in alterations to the metabolism and homeostasis in different parts of the body [5]. Cancer cachexia ultimately affects the skeletal muscle, but its effect is also found in other tissues, such as the cardiac muscle and liver [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation